2020
DOI: 10.1001/jamaoncol.2020.2394
|View full text |Cite
|
Sign up to set email alerts
|

Association of Treatment Adherence With Oncologic Outcomes for Patients With Rectal Cancer

Abstract: IMPORTANCE Despite numerous published phase 3 trials, the association of treatment adherence with outcomes for patients with rectal cancer remains largely unexplored.OBJECTIVE To analyze the association of treatment adherence with disease-free survival (DFS) among patients with rectal cancer in the CAO/ARO/AIO-04 trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…The standard decision-making pathway for rectal cancer management is based on international guidelines’ recommendations. However, the possibility to adhere to standard therapeutic schemes is not systematic for elderly patients due to higher risk for adverse events, complications, comorbidities, treatment-related mortality, and also due to explicit refusal of the patient to proceed or continue therapies, compared to younger patients [ 44 46 ]. European studies demonstrate that the proportion of patients with colorectal cancer treated following national guidelines varies between 53 and 90%, with patient preference (27%) and functional status (20%) the most commonly reported reasons for adjusted treatment [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard decision-making pathway for rectal cancer management is based on international guidelines’ recommendations. However, the possibility to adhere to standard therapeutic schemes is not systematic for elderly patients due to higher risk for adverse events, complications, comorbidities, treatment-related mortality, and also due to explicit refusal of the patient to proceed or continue therapies, compared to younger patients [ 44 46 ]. European studies demonstrate that the proportion of patients with colorectal cancer treated following national guidelines varies between 53 and 90%, with patient preference (27%) and functional status (20%) the most commonly reported reasons for adjusted treatment [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, patient involvement in perceiving personal preferences about the treatment is not systematic, especially in older patients [ 47 ]. Diefenhardt et al showed that in patients with rectal cancer, adherence to neoadjuvant chemo-radiotherapy was significantly associated with disease-free survival [ 44 ]. Mari et al found that adjuvant chemotherapy for locally advanced rectal cancer was associated with improved overall survival, although RCTs showed a 43 to 73% compliance rate, which may affect efficacy [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Freischlag et al demonstrated that achieving a complete radiation dose (45-50.4 Gy) was associated with lower risk of long-term mortality in patients with stage II and III rectal cancer who received neoadjuvant CRT (19). Moreover, a post-hoc analysis of the CAO/ARO/AIO-04 trial results evaluating the association between treatment adherence and oncologic outcomes showed that the patients with LARCs who had complete adherence to the neoadjuvant CRT, achieved significantly improved 3-year DFS compared to the patients with a reduced dose of neoadjuvant CRT (20). Consistent with the findings of that analysis, our present findings demonstrated that in the FP+OX group, the OS and LRFS were significantly superior in the patients who had completed their CRT compared to those who had not.…”
Section: Discussionmentioning
confidence: 98%
“…Survival was compared by determining the Kaplan-Meier curves, and the differences in survival were evaluated with the log-rank test. We defined 'incomplete CRT' as CRT with a total dose of <80% chemotherapy and/or a total dose of <45 Gy radiotherapy (19,20). The pre-CRT clinicopathological factors were dichotomized into two groups using Youden indexes, which were calculated by depicting the receiver-operating characteristics (ROC) curves, and factors associated with incompleteness of the neoadjuvant CRT were evaluated by logistic regression model analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Für die Post-hoc-Analyse der Assoziation zwischen Therapieadhärenz und DFS stratifizierten Diefenhardt et al die Teilnehmer in 3 Gruppen mit vollständiger nCRT (nCTh/50,4 Gy), fast vollständiger nCRT (80 % der konkurrierenden Chemotherapie/ ≥ 45 Gy) und unvollständiger nCRT (< 80 % der Chemotherapie oder < 45 Gy). Für die adjuvante Behandlung wurden die Patienten ebenfalls Gruppen mit kompletter, fast kompletter (alle Zyklen, reduzierte Dosis) und inkompletter Therapie (keine aCTh, Abbruch) zugeordnet [1].…”
unclassified